Impact of lesion preparation strategies on outcomes of left main PCI: The EXCEL trial. Issue 1 (27th June 2020) - Beohar, Nirat; Chen, Shmuel; Lembo, Nicholas J.; Banning, Adrian P.; Serruys, Patrick W.; Leon, Martin B.; Morice, Marie‐Claude; Généreux, Philippe; Kandzari, David E.; Kappetein, Arie Pieter; Sabik, Joseph F.; Dressler, Ovidiu; et al.
Abstract: Objectives: We examined outcomes according to lesion preparation strategy (LPS) in patients with left main coronary artery (LMCA) percutaneous coronary intervention (PCI) in the EXCEL trial. Background: The optimal LPS for LMCA PCI is unclear. Methods: We categorized LPS hierarchically (high to low) as: (a) rotational atherectomy (RA); (b) cutting or scoring balloon (CSB); (c) balloon angioplasty (BAL); and d) direct stenting (DIR). The primary endpoint was 3‐year MACE; all‐cause death, stroke, or myocardial infarction. Results: Among 938 patients undergoing LMCA PCI, RA was performed in 6.0%, CSB 9.5%, BAL 71.3%, and DIR 13.2%. In patients treated with DIR, BAL, CSB, and RA, respectively, there was a progressive increase in SYNTAX score, LMCA complex bifurcation, trifurcation or calcification, number of stents, and total stent length. Any procedural complication occurred in 10.4% of cases overall, with the lowest rate in the DIR (7.4%) and highest in the RA group (16.1%) ( p trend  = .22). There were no significant differences in the 3‐year rates of MACE (from RA to DIR: 17.9%, 20.2%, 14.5%, 14.7%; p  = .50) or ischemia‐driven revascularization (from RA to DIR: 16.8%, 10.8%, 12.3%, 14.2%; p  = .65). The adjusted 3‐year rates of MACE did not differ according to LPS. Conclusions: The comparable 3‐year outcomes suggest that appropriate lesion preparation may be able to overcome the increased risks of complex LMCA lesion morphology.